Preparation of Magnetite-Tannin Guava Leaves as Pb(II) Adsorbent - Mochamad Hafiz Ghozali Rusmana; Triastuti Sulistyaningsih (Indonesian Journal of Chemistry and Environment, 2022)
The increasing use of heavy metals in everyday life causes serious environmental pollution, one of which is the Pb(II) metal ion which is toxic to organisms. This study aimed to modify the tannins extracted from guava leaves with magnetite (Fe3O4) by coprecipitation as adsorbent of Pb(II) metal ion. The modified results were characterized using Fourier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), and X-Ray Diffraction (XRD). Metal ion levels of Pb(II) before and after adsorption were measured by Atomic Absorption Spectroscopy (AAS). The results showed that the tannins increased the magnetite-tannin crystal size from 85.17 to 155.66 nm. Modification of magnetite (Fe3O4) in guava leaf tannins is able to provide magnetic properties that facilitate post-adsorption separation. The optimum adsorption conditions were reached at pH 7 for magnetite-tannin and magnetite with optimum contact time. The adsorption of magnetite-tannin and magnetite occurred at 90 and 60 minutes. The maximum adsorption capacity of Pb(II) metal ions by magnetite-tannin is smaller than that of magnetite. Both adsorption processes followed the Langmuir isotherm pattern and Pseudo Order Two (Ho) kinetics.